Contemporary Studies in Environmental and Indigenous Pedagogies A Curricula of Stories and Place - Kulnieks, Andrejs; Longboat, Dan Roronhiakewen; Young, Kelly; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2013)
Contemporary Studies in Environmental and Indigenous Pedagogies: A Curricula of Stories and Place. Our book is a compilation of the work of experienced educational researchers and practitioners, all of whom currently work in educational settings across North America. Contributors bring to this discussion, an enriched view of diverse ecological perspectives regarding when and how contemporary environmental and Indigenous curriculum figures into the experiences of curricular theories and practices. This work brings together theorists that inform a cultural ecological analysis of the environmental crisis by exploring the ways in which language informs ways of knowing and being as they outline how metaphor plays a major role in human relationships with natural and reconstructed environments. This book will be of interest to educational researchers and practitioners who will find the text important for envisioning education as an endeavour that situates learning in relation to and informed by an Indigenous Environmental Studies and Eco-justice Education frameworks. This integrated collection of theory and practice of environmental and Indigenous education is an essential tool for researchers, graduate and undergraduate students in faculties of education, environmental studies, social studies, multicultural education, curriculum theory and methods, global and comparative education, and women$1 (Bs studies. Moreover, this work documents methods of developing ways of implementing Indigenous and Environmental Studies in classrooms and local communities through a framework that espouses an eco-ethical consciousness. The proposed book is unique in that it offers a wide variety of perspectives, inviting the reader to engage in a broader conversation about the multiple dimensions of the relationship between ecology, language, culture, and education in relation to the cultural roots of the environmental crisis that brings into focus the local and global commons, language and identity, and environmental justice through pedagogical approaches by faculty across North America who are actively teaching and researching in this burgeoning field.s
Keywords: Education; Education; Education (general).